Forschungsschwerpunkte und Zukunftsaufgaben der Historischen Geographie: Ländliche Siedlungen - Loose, Rainer (ERDKUNDE, 1982)
In the field of historical geography of the rural settlements in Central Europe many studies were produced during the past decade, some of which seem to be outstanding. The author endeavoured to catalogue them in a systematic order and to group them according to general comprehensive, methodological and thematic points of view. It was his intention to hint at the often considerable discrepancies between historical sources and the method chosen, which can lead to inadmissible conclusions when reconstructing settlement areas of bygone ages, especially when based on only one documentary source. The trend towards monism of methods was criticised, especially that of descriptive procedures. We recognize foci and specific accents on terminological questions and problems of settlement genetics. The examples quoted were meant to fight the thoughtless approach to the historic dimension in historic-geographical studies and the belief that it could be shown by some less important hints on historical dates. For a full understanding of the proceedings on the genetic settlement sector, a rather detailed knowledge of the respective social, economical and juridical backgrounds is needed, i.e. a multitude of historical facts and sociological processes must be revealed and known. The knowledge derived in this way should encourage the formulation of historic-geographical theories and simulation similar to those used in Anglo-Saxon countries.